Insulin-activated store-operated Ca2+ entry via Orai1 induces podocyte actin remodeling and causes proteinuria - Ji-Hee Kim (Nature Portfolio, 2021)
Perturbations of Ca2+ signaling in podocytes may deteriorate kidney function and eventually lead to proteinuria. Here the authors show that insulin can affect the function of the calcium regulator Ora1 in podocytes, which is critical for maintaining kidney filter integrity.